A Climate of Change? The Oil Industry and Decarbonization in Historical Perspective. Issue 1 (2019) - Boon, Marten
Abstract : Decarbonization has been identified as necessary to preventing catastrophic climate change, creating a dilemma for the global oil industry. This article examines the industry's reaction to this dilemma and focuses on its historical response to market and governmental regulatory pressure. The article argues that differing national climate policies provoked some oil companies to develop proactive decarbonization strategies. However, the continued growth of fossil fuel demand, the industry's vested interests, and the voluntary nature of climate governance have resulted in the industry taking very little meaningful action to achieve decarbonization.